The Dagger Scene:_ or_ The Plot discover'd. - Gillray, James, 1756-1815 (Humphrey, H., 1792)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Burke, Edmund, 1729-1797; Great Britain -- Politics and government -- 1760-1820